2023
DOI: 10.1021/acs.orglett.3c00035
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cyclization of peri-Diiminonaphthalenes Leading to the Formation of Benzo[de]isoquinolines and Stable Benzo[de]isoquinoliniums

Abstract: The interaction of peri-dilithionaphthalenes with organic cyanides was studied. Instead of the expected peri-diimines, the reaction leads to the formation of three types of benzo­[de]­isoquinolines. Treatment of unsubstituted 1,8-dilithionaphthalene with aromatic nitriles results in the formation of 1-amino-1,3-diaryl-1H-benzo­[de]­isoquinolines. In contrast, 4,5-dilithio-1,8-bis­(dimethylamino)­naphthalene gives an aromatic isoquinolonium cation via elimination of ammonia under the same condition. Upon treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…We believe that the selectivity of the protonation of 11 originates from the abovementioned strong conjugation of the 5‐NMe 2 group with an aromatic core: the stabilization of form 11’ boosts the basicity of the indole nitrogen on the one hand, and prevents the protonation of the non‐conjugated NMe 2 group by inducing a positive charge in close proximity, on the other hand (Scheme 5). A similar effect was previously observed in the case of cations 14 , where the conjugation of the 1‐NMe 2 group with the aromatic system also prevented the protonation of the molecule [35] . Additionally, the abovementioned “clothespin effect” in the case of 11 leads to the decrease of the basicity of the “proton sponge” moiety: the annulation of the 5‐membered cycle to the peri ‐positions of 1,8‐bis(dimethylamino)naphthalene leads to the increase of the internitrogen distance [49,51,52] .…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…We believe that the selectivity of the protonation of 11 originates from the abovementioned strong conjugation of the 5‐NMe 2 group with an aromatic core: the stabilization of form 11’ boosts the basicity of the indole nitrogen on the one hand, and prevents the protonation of the non‐conjugated NMe 2 group by inducing a positive charge in close proximity, on the other hand (Scheme 5). A similar effect was previously observed in the case of cations 14 , where the conjugation of the 1‐NMe 2 group with the aromatic system also prevented the protonation of the molecule [35] . Additionally, the abovementioned “clothespin effect” in the case of 11 leads to the decrease of the basicity of the “proton sponge” moiety: the annulation of the 5‐membered cycle to the peri ‐positions of 1,8‐bis(dimethylamino)naphthalene leads to the increase of the internitrogen distance [49,51,52] .…”
Section: Resultssupporting
confidence: 79%
“…A similar effect was previously observed in the case of cations 14, where the conjugation of the 1-NMe 2 group with the aromatic system also prevented the protonation of the molecule. [35] Additionally, the abovementioned "clothespin effect" in the case of 11 leads to the decrease of the basicity of the "proton sponge" moiety: the annulation of the 5-membered cycle to the peri-positions of 1,8bis(dimethylamino)naphthalene leads to the increase of the internitrogen distance. [49,51,52] Indeed, performed quantum chemical calculations (for R = tert-Bu) have demonstrated that formation of form 15 is thermodynamically less favourable than 11 • H + : ΔΔG (11 g • H + !15 g) = + 8.0 kcal/mol (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations